An Improved Energy Efficient Scheme for Scheduling Mobile Sensors in a Hybrid Wireless Sensor Networks with Obstacle Avoidance (International Journal of Engineering and Computer Science, 2015)
Advancement of robotic technologies as well as wireless communication led to the development of  hybrid sensors which consist of static sensors and mobile sensors. Static sensors are the traditional sensors used for sensing physical and environmental characteristics while mobile sensors have powerful sensing capabilities so that  it can move anywhere at any time. Each static and mobile sensors can analyze multiple attributes of events. However, such a high mobility may cause scheduling problems. The critical issue is the dispatching of multi attribute mobile sensors to the multi attribute event location appearing in sensing field while considering obstacles and also balance the energy consumption and increase the lifetime of wireless sensor network. Here an improved MAM sensor dispatching algorithm is proposed for developing an energy efficient solution.